""Buried among the ruins": Gissing and the Sorcery of Athens." - Mitsi, Efterpi (Victorians: A Journal of Culture and Literature, 2021)
George Gissing's novel Sleeping Fires (1895) presents a late nineteenth-century Athens that is divided between its ancient and modern identities. As a reflection on the significance of Hellenism in Victorian culture, the novel narrates the random encounter between Edmund Langley, a self-exile with a classical education, and Louis Reed, a passionate and radical young man, who is revealed to be Langley's lost and unknown son. In the context of Gissing's diaries and letters recording his visit to Athens, Sleeping Fires portrays the city as an ambivalent space, both inspirational and deceptive. Gissing's juxtaposition of the ancient monuments' beauty with the bleakness of their modern surroundings emphasizes the distance between antiquity and modernity as well as Victorians' misinterpretations of Greece, revealing the period's conflicting discourses about Hellenism.